Fructooligosaccharides (FOS) differentially modifies the in vitro gut microbiota in an age-dependent manner - Mahalak, Karley K.; Firrman, Jenni; Narrowe, Adrienne B.; Hu, Weiming; Jones, Steven M.; Bittinger, Kyle; Moustafa, Ahmed M.; Liu, LinShu (Frontiers in Nutrition, 2023)
Fructooligosaccharides (FOS) are well-known carbohydrates that promote a healthy gut microbiota and have been previously demonstrated to enhance levels of Bifidobacterium and Lactobacillus. Its bifidogenic properties are associated with positive health outcomes such as lowered obesity and anti-inflammatory properties, and, therefore, is in use as a prebiotic supplement to support healthy gut microbiota. However, the gut microbiota changes with age, which may lead to different responses to treatments with prebiotics and other dietary supplements. To address this concern, we implemented a 24-hour in vitro culturing method to determine whether FOS treatment in 3 different adult age groups would have a differential effect. The age groups of interest ranged from 25-70 years of age and were split into young adults, adults, and older adults for the purposes of this analysis. The cultured communities were subject to 16s rRNA sequencing to determine the structure and LC-MS/MS analysis to measure short-chain fatty acid (SCFA) levels, which is an indicator of community function. qPCR analysis targeting Bifidobacterium was applied to measure the enhancing effect of FOS on this taxon. The results of this study demonstrate the positive effects of FOS on the gut microbiome, and importantly, how age may play a role in the effectiveness of this prebiotic.